Is Perceived Autonomy Support Provided by a Coach Related to the Intention of Injury Preventative Behavior Among National and International Level Golfers? - Parker, James; Johnson, Urban; Ivarsson, Andreas (Frontiers in Sports and Active Living, 2021)
The successful implementation of injury prevention programs is reliant on athletes and coaches accepting, adopting, and complying with injury preventative behaviors that reduce injury risk. Exploring factors, such as motivation and planned behavior, that might increase the frequency of preventive behaviors warrants investigation. The aim of the study was to investigate the association between self-determined motivation and intention of injury preventative behavior among high-level golfers. A total of 60 golfers completed questions on psychological measures of perceived autonomy support from coaches, autonomous motivation, and intentions of injury preventative behavior. A neural network model analysis was performed to investigate the strength of connection between covariates and construct a network structure. Analysis of results was performed by assessing edge strengths and node centrality to guide inference of the network topology. The result showed one cluster comprising positive associations between perceived autonomy support, effort of injury preventative behavior, and frequency of injury preventative behavior. When aiming to encourage injury preventative behavior, coaches should consider giving feedback that supports autonomous motivation since it is positively associated with effort and frequency of injury preventative behavior among high-level golfers. Injury prevention programs should include strategies to improve the athlete’s autonomous motivation to carry out preventive activities.